2014
DOI: 10.3758/s13423-014-0789-9
|View full text |Cite
|
Sign up to set email alerts
|

At will or not at will: Electrophysiological correlates of preparation for voluntary and instructed task-switching paradigms

Abstract: The present study investigated whether the advanced reconfiguration processes of the voluntary switching (VTS) paradigm were different from those of the instructed task switching (ITS) paradigm by examining event-related potentials (ERPs) in a within-subjects design. Of importance, given that effector-to-task mapping might lead to differential preparatory strategies, two effector-to-task mapping groups were studied: the hand-to-task (HAND) and finger-to-task (FINGER) groups. Intriguingly, we found the increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 32 publications
1
20
2
Order By: Relevance
“…In line with evidence from both voluntary task switching (Poljac & Yeung, 2014) and forced task switching (Karayanidis et al, 2011;but see Lavric et al, 2008), this effect seemed dissociable from the posterior positivity, as it was not significantly influenced by task transition and differed significantly between choice types. However, the effect is not in line with previous ERP studies on voluntary task switching (Chen & Hsieh, 2015;Kang et al, 2014;Poljac & Yeung, 2014;Vandamme et al, 2010) that found a (transition-dependent) enhancement on voluntary trials. A possibility for the diverging effects could be the different stimulus types.…”
Section: Commonalities and Differences Of Forced And Voluntary Task S...contrasting
confidence: 98%
See 2 more Smart Citations
“…In line with evidence from both voluntary task switching (Poljac & Yeung, 2014) and forced task switching (Karayanidis et al, 2011;but see Lavric et al, 2008), this effect seemed dissociable from the posterior positivity, as it was not significantly influenced by task transition and differed significantly between choice types. However, the effect is not in line with previous ERP studies on voluntary task switching (Chen & Hsieh, 2015;Kang et al, 2014;Poljac & Yeung, 2014;Vandamme et al, 2010) that found a (transition-dependent) enhancement on voluntary trials. A possibility for the diverging effects could be the different stimulus types.…”
Section: Commonalities and Differences Of Forced And Voluntary Task S...contrasting
confidence: 98%
“…Studies using other designs offer support for this rather universal finding of the switch positivity in task switching, as it was similarly found in intermittently instructed cued task switching (Barceló et al, 2007), in both response-effector and stimulus-dimension shifts (Hsieh et al, 2014), and with transition instead of task cues (West et al, 2011). More importantly, against the background of methodologically diverse and hence partially contradicting ERP studies in voluntary task switching (Chen & Hsieh, 2015;Forstmann et al, 2007;Kang et al, 2014;Orr et al, 2010, November;Poljac & Yeung, 2014;Vandamme et al, 2010), the current results offer strong support that switch preparation under forced-and voluntary-choice conditions is very similar, after all. Some authors suggested that in order to perform a successful task switch, the cognitive system has to reconfigure the currently active set of task representations in order to match the now relevant task (Monsell, 2003).…”
Section: Commonalities and Differences Of Forced And Voluntary Task S...mentioning
confidence: 63%
See 1 more Smart Citation
“…Moreover, estimation of individual switch costs with the training blocks data might be subject to extra noise because participants need time to familiarize themselves with the experimental setting and the single tasks. It is also an open question whether the Bbaseline^measure of switch costs with the alternating-run training procedure used here is suitable to represent switching limitations that are supposedly also present in the voluntary task-switching blocks: Although the substantial positive correlations between training and voluntary switch costs indeed suggest that these limitations rely on similar processes, it should be noted that even switch costs in procedures differing only in how task order is determined (i.e., explicit cuing vs. alternating runs) should not be treated as identical measures (Altmann, 2007), and many studies found that voluntary switch costs are often smaller than switch costs in externally controlled task switching (e.g., Arrington & Logan, 2005;Chen & Hsieh, 2015;Demanet & Liefooghe, 2014;Orr & Weissman, 2011). Thus, all correlational data (i.e., correlations within the voluntary switching blocks and between training and voluntary switching blocks) must be interpreted with caution, and future studies with larger samples are clearly needed if researchers wish to investigate individual differences with the present paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…Cuing distractor identity immediately before search onset may fail, therefore, because it provides only very weak task set instantiation. The task-switching literature has shown that voluntary choice designs in which participants choose what they will respond to, allow for optimal task set preparation when compared to trial-by-trial cuing paradigms (Arrington & Logan, 2005;Chen & Hsieh, 2015). This was confirmed with a comparison of a cuing and a voluntary choice variant of matched attention capture tasks, using the pre-stimulus CNV component as an index of proactive task set preparation (Henare et al, 2020).…”
Section: Commentarymentioning
confidence: 82%